2016
DOI: 10.1002/adfm.201503940
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Enhancement in Solution‐Processed Transparent Conductive Oxide TFTs due to Electron Donation from Traps in High‐k Gate Dielectrics

Abstract: High‐mobility ZnO thin films are deposited onto solution‐processed ZrO2 dielectrics in order to investigate the large differences between experimental field‐effect mobility values obtained when transparent conductive oxide (TCO) materials are deposited onto high‐k dielectrics as opposed to thermally grown SiO2. Through detailed electrical characterization, the mobility enhancement in ZnO is correlated to the presence of electron traps in ZrO2 serving to provide an additional source of electrons to the ZnO. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 34 publications
6
71
1
Order By: Relevance
“…Furthermore, here we are not claiming that the benefits to electron mobility stem from the formation of a two‐dimensional electron gas at the interface as has been previously argued, even in thick (340 nm) InGaZnO films . Instead, similar to previous observations made in the ZnO/ZrO 2 system , we explain the mobility enhancement in a semiconductor/insulator heterostructure based on directional electron transfer from the Ga 2 O 3 to the ZnO, supported by work function differences obtained for the isolated films as a function of processing temperature. This also provides additional experimental evidence supporting the existing observations in the literature with regard to TCO/high‐k interactions.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, here we are not claiming that the benefits to electron mobility stem from the formation of a two‐dimensional electron gas at the interface as has been previously argued, even in thick (340 nm) InGaZnO films . Instead, similar to previous observations made in the ZnO/ZrO 2 system , we explain the mobility enhancement in a semiconductor/insulator heterostructure based on directional electron transfer from the Ga 2 O 3 to the ZnO, supported by work function differences obtained for the isolated films as a function of processing temperature. This also provides additional experimental evidence supporting the existing observations in the literature with regard to TCO/high‐k interactions.…”
Section: Introductionsupporting
confidence: 81%
“…Although this effect is very reliably reproduced experimentally , its precise cause is only beginning to be understood. This lack of understanding has led to recent attempts to identify a physical origin .…”
Section: Introductionmentioning
confidence: 99%
“…The trap density at/near the gate-dielectric/ ZnO interface can be estimated by equation (3) to be 1.6×10 12 , 1.2×10 12 and 3.6×10 12 cm −2 for the annealing temperature of 200°C, 300°C and 400°C, respectively, indicating that the relatively good electrical performance of the ZnO-TFT with the annealing temperature of 300°C is mainly attributed to the low trap density at/near the gate-dielectric/ZnO interface. In addition, the devices for the three annealing temperatures exhibit a low voltage operation (<8 V), which is close to the results reported using Al 2 O 3 and Ta 2 O 5 gate dielectrics [11,27], but is higher than that of HfLaO and ZrO 2 gate dielectrics [19,20], implying that the electrical performances of the device need to be further optimized for the requirement of low power application in flexible and wearable electronics. Figure 4 exhibits the hysteresis behavior of transfer characteristics under forward and reverse V GS sweeps, and the threshold-voltage shifts (ΔV th =V th·reverse −V th·forward ) of the samples with different NbLaO annealing temperatures are listed in table 1.…”
Section: Resultssupporting
confidence: 82%
“…Su et al [19] fabricated ZnO TFTs with HfLaO gate dielectric, which resulted in a low operating voltage <3 V and a carrier mobility of 3.5 cm 2 V −1 s −1 . Subramanian et al [20] explored solution-processed ZrO 2 gate dielectric and demonstrated a mobility of 20 cm 2 V −1 s −1 and a low operating voltage <3 V in ZnO TFTs. However, there are several potential disadvantages associated with using high-k gate dielectric in TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the heat issue, [8,11] power dissipation, [7,77] lithographic accuracy, [9] and quantum limit [10] problems will substantially increase the economic costs of further circuit integration, in line with Moore's law. [78][79][80] Significantly, the ferroelectric layer inserted in the gate stack is not only a kind of high-κ electric, but also can prevent the gate leakage effectively by NC effect. High thermal dissipation not only increases energy loss but also weakens the working performance of devices.…”
Section: Moore's Law Facing Severe Challengesmentioning
confidence: 99%